An Assessment of Urban Change and Its Drivers in Suleja Local Government Area of Niger State, Nigeria - Adeleye, Bamiji Michael; Ssemwogerere, Kenneth; Mukwaya, Paul Isolo; Kiggundu, Amin Tamale; Omolo-Okalebo, Fredrick; Kayondo, Lydia Mazzi (CSID Journal of Infrastructure Development, 2023)
The knowledge of urban change is critical to the management and planning of urban areas. Robust geospatial technologies have increasingly enhanced our understanding of urban change. This paper employs remote sensing and GIS data from the earth explorer data archive to assess the character and pattern of urban change in Suleja Local Government Area (Niger State in Nigeria) and its drives from 1987 to 2019. The nature and character of urban change are examined from the lens of the urban intensity index and the urban land use/cover change. Data from the geospatial techniques were corroborated with secondary data from the Niger State Regional Plan, Suleja Master Plan, and the Abuja Master Plan. The underlying drivers of urban change within this period were also examined. This study reveals that Suleja Local Government Area experienced unprecedented growth in its urban area from 1987 to 2019. Using Qiuying's mathematical model for the urban change intensity index, the study revealed that the urban change intensity index of Suleja developed from low urban intensity (0.16) to highly rapid urban intensity (0.73). The highly rapid urban intensity index witnessed in Suleja was dominated by an edge expansion urban form of change associated with urban sprawl. This study further reveals that the present physical development activities in Suleja are not sustainable. This study, therefore, recommends articulated urban planning for Suleja LGA; also, the outdated Niger State Regional Development Plan and Suleja Master Plan should be reviewed by the Niger State Government.